Water-based single-flow mixing condensation particle counter. Issue 12 (1st December 2016) - Romay, Francisco J.; Collins, Aaron M.; Dick, William D.; Li, Lin; Fandrey, Chris W.; Liu, Benjamin Y. H.
ABSTRACT: A novel water-based condensation particle counter has been developed using a patented, single-flow mixing (SFM) condenser that permits a conventional thermal approach of using a hot saturator followed by a cold condenser to activate and grow particles for counting with an optical detector. A computational fluid dynamics (CFD) model of the internal flow, temperature, and vapor profiles was used to predict the effectiveness of the SFM condenser. Using the results from the CFD model, the counting efficiency was numerically calculated for pure water droplets, and the CPC cut-point (i.e., 50% counting efficiency) was predicted to be 8.3 nm. The experimental performance of the new CPC was measured with differential mobility analyzer-classified, monodisperse particles. The measured cut-points were 8.2 nm for Ag particles and 3.9 nm for NaCl particles. The reduction in the cut-point for NaCl is the result of a compound effect: water uptake by NaCl particles, which increases their size before entering into the growth section (condenser), and the reduction of the equilibrium vapor pressure of water over NaCl-water droplets, resulting in a decrease of the activation diameter. Copyright © 2016 American Association for Aerosol Research